The major coat protein gene of the filamentous Pseudomonas aeruginosa phage Pf3: absence of an N-terminal leader signal sequence. - Luiten, R G (1983)
From in vitro protein synthesis studies and nucleotide sequence analysis it has been deduced that, unlike the major coat proteins of the hitherto studied filamentous bacterial viruses Ff (M13, fd and f1), IKe and Pf1, the major coat protein of the filamentous Pseudomonas aeruginosa virus Pf3 is not synthesized as a precursor containing a leader signal polypeptide at its N-terminal end. From the elucidated nucleotide sequence of the Pf3 major coat protein gene it follows that the coat protein is 44 amino acid residues long (mol.wt. 6425). No sequence homology was observed with the major coat protein genes of either the Ff group or IKe but, similar to these phages, 3' ward of the Pf3 coat protein gene a DNA sequence is located which has many characteristics in common with rho-independent transcription termination signals.